Pengaruh Kompensasi dan Tingkat Disiplin Kerja - Nita Novianti, Nita; Indah Octavia, Intan; Indirawati, Dinda; Sanusi, Sanusi; Ihsan , Mohamad (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
Human Resource Management by a company or organization is very necessary. This is because Human Resources are the main force in the success of a company or organization in achieving its goals. The consequences of poor HR management will be very visible and can be detrimental to the company or organization, such as decreased employee performance which can result in it being difficult to achieve the goals of the company or organization. Therefore, further research studies are needed regarding forms of HR management to improve employee performance. In this research, the author focuses on one form of HR management, namely compensation and work discipline, by examining further how compensation and the level of work discipline influence employee performance, especially in startup companies.